Carrie and me [large type] : a mother-daughter love story - Burnett, Carol (Center Point Large Print, 2013)
In Carrie and Me, Carol Burnett shares her personal diary entries and correspondence revealing her anguish as a mother of a troubled teenager, the epiphanies that helped her help her family, and the grief and then the hope she felt after Carrie's death. Through Burnett's inimitable voice, we get a portrait of an unforgettable young woman that will bring hope to anyone struggling with raising or losing a child.